Ett enande band bland Nordens alla samer: Slöjd på Samernas folkhögskola/Sámij álmmukallaskåvllå - Hansson, Johan (Educare, 2019)
From its establishment in 1942, the Sami folk high school included crafts as an important part of its education program. The Swedish Mission Society, who founded the school, not only wanted to educate Sami youth to better their chances on the labour market but also to give them the opportunity to get acquainted with their Sami culture. Thus Sami crafts had a crucial role in educational activities at the folk high school. With the help of Gert Biesta’s concepts, the article shows that crafts had a socializing function. The teaching strengthened the students’ collective identity and provided them with traditional skills and knowledge. However, Lennart Wallmark, the school principal (1942-1972), stressed the importance of learning crafts for other purposes. Influenced by religious thinkers, he stated that the students would also be strengthened as individuals: a process of subjectification. Moreover, the crafts lessons had a third function: qualification. Though the studies were not vocational as such, they could simplify the process of procuring the quality label bestowed by the Sami organization Same Ätnam to crafts of especially high quality. Wallmark and the teachers in crafts were important for the development of craft education at the folk high school. However, Same Ätnam’s ideas of Sami handicraft and government regulations were also influential. These inner and outer forces contributed to the teaching so that it, on one hand, did not change much but, on the other hand, was congruous with the rest of the society.